The interplay between technological innovation and human capital development in driving industrial productivity and competitiveness in Africa - Segun Subair Awode; Musa Olanrewaju Oduola (Journal of Economics and Development)
Purpose – This study examines how technological innovation (TECIN) and human capital development (HCD) combine to impact industrial productivity (INPR) and competitiveness in Africa. Design/methodology/approach – The study used secondary data covering the period from 1996 to 2021 on 36 African countries, in a panel data framework of fixed effect and generalized method of moments techniques. Findings – The study found that while TECIN negatively affected INPR in Africa, HCD exerted a strong positive influence. The interaction of TECIN and HCD showed a joint positive impact on INPR, emphasizing the role of human capital in mitigating transitional productivity loss tied to new technology assimilation. The results also showed positive individual and combined effects of TECIN and HCD on industrial competitiveness in Africa. Practical implications – The findings therefore compel the need for implementation of policies that can simultaneously advance TECIN and strengthen HCD for sustainable industrial development in Africa. Governments in African countries need to allocate more resources to research and development to foster home-grown technologies, revamp educational curricula to align with industry needs and emphasize practical skills training, and facilitate technology transfer partnerships to enhance technological capabilities and INPR. Originality/value – Although previous studies acknowledge the importance of TECIN and HCD for enhancing INPR and competitiveness in Africa, there is a noticeable lack of comprehensive studies that investigated the interplay between TECIN and HCD for industrialization gains.